Adverse perinatal outcome in diabetic mother treated with oral hypoglycemic agents vs. insulin - Das, Leena; Meher, Bijay Kumar; Parida, Sagar; Pradhan, Deepti Damayanty; Das, Lucy; Jena, Umesh Chandra (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Insulin has been the primary mode of therapy in diabetic mother for glycemic control as oral hypoglycemic agents (OHA) were initially thought to have teratogenic effect. Recent data supports the use of certain OHA; this study was designed to compare the perinatal outcomes in infants born to diabetic mother treated with insulin vs. oral hypoglycemic agents and to find out the relation of adverse perinatal events to glycemic control in both groups. Methods: This prospective observational study was conducted in a tertiary care hospital. 108 neonates born to diabetic mother between October 2014 to September 2016 were taken for study immediately after delivery after excluding the mothers who were treated with lifestyle modification and/or dietary modification alone only. 60 mothers had received insulin and 48 OHA for glycaemic control. Glycemic control was assessed by HbA1C estimation on the day of delivery. The infants were followed up in neonatal care unit for perinatal complications. Main outcome measure(s): birth weight, gestational age, respiratory problems, birth injury, birth asphyxia, congenital anomalies, hypoglycemia, hypocalcaemia, hyperbillirubinemia. Results: Out of 108 infants, 27 were born to pregestational and 81 to gestational diabetic mothers. 60(55.5%) were treated with insulin and rest with OHA, 53(49.1%) had optimal glycemic control. Both the groups had similar glycemic control in the third trimester. None of the perinatal outcomes showed significant difference between insulin and OHA group except neonatal hyperbillirubinemia. (p=0.013, RR=8 and OR=0.106). Within the optimal glycemic control (HbA1C <8), LGA has significant association with the insulin group than OHA (p=0.012, RR=2.217 and OR=4.2018). Conclusions: As compared to insulin, oral hypoglycemic agents have similar glycemic control and no adverse perinatal outcomes and can be used in pregnant mothers with diabetes mellitus from poor socioeconomic and educational background for its low cost and better patient compliance. Within the glycemic control, maternal treatment with insulin showed significant difference in LGA compared to OHA which needs further studies for validation.